ACTION OF IMAZETHAPYR AND LACTOFEN ON THE NODULATION OF CONVENTIONAL AND TRANSGENIC SOYBEAN UNDER DROUGHT STRESS CONDITIONS - Goncalves, C. G.; Silva Junior, A. C. [UNESP]; Scarano, M. [UNESP]; Pereira, M. R. R.; Martins, D. [UNESP] (Univ Federal Vicosa, 2018)
This research aimed at studying the action of the herbicides imazethapyr and lactofen on the root system and rhizobium/plant interaction, when they are sprayed at two phenological development stages of soybean cultivars under different soil water management. The soybean cultivars MG/BR 46 Conquista (conventional) and BRS Valiosa (RR) were submitted to three minimum soil water potential (Psi s): -0.03; -0.07 and -0.5 MPa at the V2 and V4 phenological stages. The herbicides imazethapyr at the rate (100 g a.i. ha(-1)) and lactofen at the rate (180 g a.i. ha(-1)) were sprayed 10 days after the start of water restrictions. Twenty-one days after the application of the herbicides, root dry matter and root nodulation were evaluated. The BRS Valiosa (RR) soybean cultivar presented better nodule formation and a more efficient and more adapted root system to support moderate drought stress conditions (-0.07 MPa). The MG/BR 46 Conquista (conventional) soybean cultivar presented lower the root system growth when submitted to the spraying of imazethapyr and lactofen. The activity of N-2-fixating bacteria was affected by the spraying of the herbicides imazethapyr and lactofen.
Keywords: ALS; Glycine max; phytotoxification; PROTOX; symbiotic fixation of N-2